Mangrove Diversity along the Coast of Ratnagiri, Maharashtra - Mulla, Tarnnum Mubarak; Suneel Chavan, Niranjana (Current Botany, 2017)
The present paper deals with the study of mangrove diversity along different sites of Ratnagiri coast of Maharashtra, India. Height of the plants, Importance Value Index and various indices viz. Simpsonâ€™s index, Shannon-weaver index and Margalef index were determined. Maximum height was recorded from Chinchkhari site (8.76 meters). It was observed that the Sonneratia alba, Avicennia marina and Ceriops tagal species showed the highest Importance Value Index from respective sites. Based on ecological indices, Narayanmali site was found to be rich in diversity while other sites are encroached and destructed mostly by anthropogenic activities. The piece of work is significant in comparing the diversity at micro level by monitoring periodically for future programs.Â